Lifðu. Nóvella - Sigríður H Jónasdóttir 1983- (2020)
Nóvellan Lifðu er meistaraverkefni í ritlist við Háskóla Íslands. Hún fjallar um missi móður og sonar. Móðirin syrgir son sinn, Frosta, sem lést nokkrum árum áður en sagan hefst, en Frosti syrgir eigið líf. Frosti gengur aftur og ásækir móður sína í tvær vikur á ári því hann kennir henni um veikindin sem drógu hann til dauða The novella Live is a master's thesis in creative writing at the University of Iceland. It deals with the loss of a mother and her son. The mother mourns her son, Frosti who died a few years before the story begins. Frosti returns to haunt his mother for two weeks each year as he mourns the loss of his life, he blames his mother for the illness that caused his death